Karakterisasi Bio-Oil dari Hasil Pirolisis terhadap Biomasa - Dewi Selvia Fardhyanti; Astrilia Damayanti; Amalia Larasati (Seminar Nasional Teknik Kimia Kejuangan, 2017)
The utilization of biomass as a source of new and renewable energy is being carried out. One of the technologies to convert biomass as an energy source is pyrolysis which is converting biomass into more valuable products, such as bio-oil. Bio-oil is a liquid which produced by steam condensation process from the pyrolysis of coconut shell. The composition of biomass such as hemicellulose, cellulose and lignin will be oxidized to phenol, alcohol, and acetate acid as the main content of the bio-oil. The experiments typically occurred at the atmospheric pressure in a laboratory furnace at temperatures ranging from 300 to 550oC with a heating rate of 10oC/min and a holding time of 1 hour at the pyrolysis temperature. The Gas Chromatography-Mass Spectroscopy (GC-MS) was used to analyze the bio-oil components. The obtained bio-oil has the viscosity of 1.185 cp (coconut husk), 1.133 cp (coffee husk), 1,094 cp (sawdust); the density of 1.008 g/cm3 (coconut husk), 0.994 g/cm3 (coffee husk), 0.98 g/cm3 (sawdust);the caloric value of 3500kcal/kg (coconut husk),4200 kcal/kg (coffee husk), 1500 kcal/kg (sawdust); and the moisture content of 16% (coconut husk),31% (coffee husk),13% (sawdust). The analysis of GC-MS result showed that the bio-oil from coconut husk contained ethyl ester (37.60%), phenol (40.01%); bio-oil from coffee husk contained acetic acid (26%), phenol (34%); and bio-oil from sawdust contained acetaldehyde (26.15%), acetic acid (20.90%).